(untitled) (Research, Society and Development, 2025)
Melanoma is a type of skin cancer that originates in melanocytes and can manifest itself in any region of the body in the form of spots, nevi or moles. It accounts for 3% of cutaneous neoplasms and has a high metastatic capacity and mortality rate. The aim of this study was to assess the benefits of immunotherapy on progression-free survival and overall survival in relation to the standard therapy available for the treatment of metastatic melanoma in the Unified Health System (SUS). A narrative review was carried out, analyzing 18 scientific articles selected from the PubMed, Cochrane and Scielo databases, covering the last 10 years. The inclusion criteria were complete articles in Portuguese, English or Spanish, including systematic reviews, meta-analyses and cohort or randomized studies. The data obtained reinforces the greater efficacy and lower toxicity of immunotherapy compared to chemotherapy with dacarbazine in the treatment of metastatic melanoma, highlighting it as a promising therapeutic alternative. Despite the superior clinical outcome of immunotherapy over chemotherapy with dacarbazine, especially with regard to progression-free survival and overall survival, challenges remain regarding its widespread implementation in the SUS, especially in the financial sphere. This highlights the need to develop strategies aimed at democratizing access to immunotherapy in the context of metastatic melanoma, since, despite the high cost, the benefit for patients with advanced metastatic melanoma is undeniable, with a significant improvement in quality of life.